Pelaksanaan Strategi Thinking A Loud Pairs Problem Solving (TAPPS) untuk Meningkatkan Aktivitas dan Hasil Belajar Bahasa Indonesia pada Siswa Kelas XI IPK.1 MAN 2 Pessel - Jusmaini Jusmaini (Departement of Mathematics Education, 2023)
This study aims to describe the increase in activity and student learning outcomes in learning Indonesian in class XI. GPA 1 MAN Pessel through the implementation of the TAPPS strategy. This type of research uses classroom action research. This research is reflective in nature by increasing classroom learning in a more professional manner. The main goal is that the problems that occur can be overcome so that they can increase the activity and learning outcomes of class XI students. GPA 1 MAN 2 Pessel academic year 2020/2021 in learning Indonesian. The subjects in the study were class XI students. GPA 1 for the 2020/2021 academic year, a total of 29 people. The results of the study show that the implementation of the TAPPS strategy can increase student learning activities according to the indicators that are the object of observation. In addition, the implementation of the TAPPS strategy can improve student learning outcomes, namely in the implementation of cycle 1 the average student learning outcomes increase to 79.65 to 87.58 in the implementation of cycle 2.